Cutaneous melanoma: new advances in treatment - Michele Ceolin Foletto; Sandra Elisa Haas (Sociedade Brasileira de Dermatologia, 2014)
Cutaneous melanoma is a challenge to treat. Over the last 30 years, no drug or combination of drugs demonstrated significant impact to improve patient survival. From 1995 to 2000, the use of cytokines such as interferon and interleukin become treatment options. In 2011, new drugs were approved by the U.S. Food and Drug Administration, including peginterferon alfa-2b for patients with stage III disease, vemurafenib for patients with metastatic melanoma with the BRAF V600E mutation, and ipilimumab, a monoclonal antibody directed to the CTLA-4 T lymphocyte receptor, to combat metastatic melanoma in patients who do not have the BRAF V600E mutation. Both ipilimumab and vemurafenib showed results in terms of overall survival. Other trials with inhibitors of other genes, such as the KIT gene and MEK, are underway in the search for new discoveries. The discovery of new treatments for advanced or metastatic disease aims to relieve symptoms and improve patient quality of life.